Boston - Grant, Kimberly (Hawthorn, Victoria Lonely Planet Publications, 2000)
Featuring five original walking tours of the city neighbourhoods and details on Boston's hot spectator sports scene, this guide to the city also includes details of excursions along the New England coast and shopping trips to Maine.
Title from cover.
At head of title: Lonely Planet.
"From the Tea Party to the T."--Cover.
Keywords: Boston (Massachusetts) -- Guidebooks; Massachusetts -- Boston